Isolation of Antithrombotic Phenolic Compounds from the Leaves of Crataegus pinnatifida - Song, Shao-Jiang; Li, Ling-Zhi; Gao, Pin-Yi; Yuan, Yan-Qiang; Wang, Ru-Ping; Liu, Ke-Chun; Peng, Ying (Planta Medica, 2012)
Four novel phenolic compounds (1–4) were isolated from the leaves of Crataegus pinnatifida, along with three known ones (5–7). Their structures were elucidated as: methyl 4-O-β-D-glucopyranosyl-3-[(2E,6E)-8-O-β-D-glucopyranosyl-3,7-dimethyl-2,6-octadienyl] benzoate (1), biphenyl-5-ol-3-O-β-D-glucoside (2), 3,4′-dimethoxy-biphenyl-5-ol-4-O-β-D-glucoside (3), (E)-6-(benzoyloxy)-1-hydroxyhex-3-en-2-O-β-D-glucoside (4), shanyenoside A (5), eriodectyol (6), and 2″-O-rhamnosyl vitexin (7), using a combination of mass spectroscopy, 1D and 2D NMR spectroscopy, and chemical analysis. The antithrombotic activity of the isolated compounds was investigated on the transgenic zebra fish system. Among them, eriodectyol (6) potently inhibited the production of thrombus.
Keywords: Crataegus pinnatifida; Rosaceae; phenolic compounds; antithrombotic activity